Multifocal conjunctival leaks due to the use of mitomycin C mimicking the normal drainage of the tear from the lacrimal excretory ducts - Turgut, Burak; Kaya, Murat; Demir, Tamer; Aydemir, Orhan; Cobanoglu, Bengue (Dove Medical Press Ltd, 2010)
A 20-year-old male patient underwent trabeculectomy with mitomycin C (MMC) because of glaucoma secondary to the use of corticosteroid drops. There were three conjunctival holes, which had a positive Seidel test, near the superior fornix three weeks after surgery. Because of hypotony and choroidal effusion in the operated eye, the patient was hospitalized and medical treatment carried out. Despite medical treatment, the leak continued for ten days. The conjunctiva was then partially excised and the tissue was subjected to histopathological evaluation. The conjunctiva and Tenon's capsule were sutured and the Seidel test was negative, intraoperatively. The histopathological examination of the tissue showed necrosis due to MMC. The excising of conjunctival necrotic tissue provided successful control of intraocular pressure and the patient became asymptomatic at six months follow-up. It should be considered that a leak from superotemporal conjunctiva near the fornix after trabeculectomy with MMC may be confused with orifices of the lacrimal gland ducts.
Keywords: trabeculectomy with MMC; conjunctival necrosis; leak